Effect of Pasak Bumi (Eurycoma longifolia Jack) Root In Precopulation Stage to the Fertility of Female Mouse (Mus musculus L.) - Marlinza, Rosa (Universitas Jambi, 2009)
Pasak Bumi (Eurycoma longifolia Jack) have potency to be used to increase bodyendurance, to cure malaria drug, and to act as afrodisiak. However, the effect of pasak bumi onwomen fertility, especially at pre-copulation stage was not widely known. This research seeks toreveal the effect pasak bumi extract treated at pre-copulation phase on fertility. This experimentemploy mice (Mus Musculus L.) and was undertaken at Biology and Cemistry laboratories PMIPA, andVeterinary laboratory of Jambi University, from November 2008 until January 2009. We used acompletely randomized design with four treatments and 6 replications: The treatments were K: controlwithout extract, E200 (200 mg/kg BW/day), E400 (400 mg/kg BW/day), and E600 (600 mg/kg BW/day).The extract is goven orraly within 10 succesive days of pre-copulation phase. We performed surgeryon the mice on 18th date of pregnancy. Observation parameters were focused on body weight, totalimplantations, and foetus percentage. The results show that Pasak bumi root extract treatment at precopulationstage does not affect total implantation declining, fetus weight, and mice body weight.However, the treatment significantly effect percenatege of lived fetus, and ovary weight.